Photobiomodulation Therapy at 660 nm Inhibits Hippocampal Neuroinflammation in a Lipopolysaccharide-Challenged Rat Model - Tae-Mi Jung; Jong-Ha Lee; Jin-Chul Heo; Chang-Hyun Kim (Biomedicines)
Background/Objectives: Neuroinflammation is associated with the progression of various brain diseases, and the management of neuroinflammation-induced neural damage is a crucial aspect of treating neurological disorders. This study investigated the anti-inflammatory efficacy of photobiomodulation therapy (PBMT) using 660 nm phototherapy in a rat model with lipopolysaccharide (LPS)-induced neuroinflammation. Methods: We induced inflammation in rat brains via intraperitoneal injection of LPS and subjected the treatment group to 660 nm phototherapy to examine its protective effect against hippocampal damage based on pathological, histological, and immunohistochemical tissue analyses. Results: The 660 nm treated rats showed a significant decrease in hippocampal structural damage and cell death compared to the LPS-treated group. We observed reduced expression of the inflammation markers GFAP, TNF-α, and IL-1β in the hippocampus of the treatment group, and an increase in SIRT1 expression across all hippocampal regions. Conclusions: This study presents a promising method for controlling neuroinflammation and providing neuroprotection and inflammation relief. PBMT represents a non-invasive therapeutic approach with minimal side effects ensured through the proper control of light irradiation.